2013
DOI: 10.4236/ojra.2013.32013
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystemic involvement and diverse manifestations. Neuropsychiatric systemic lupus erythematosus (NPSLE) is a complex neurological disorder characterized by neuropsychological dysfunction. NPSLE is associated with increased morbidity and mortality. In 1999, the American College of Rheumatology developed 19 discrete neuropsychiatric syndromes that comprised NPSLE. Nervous system disease in systemic lupus erythematosus is mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune multifactorial disease characterized by multisystemic involvement and diverse clinical features [104]. Involvement of the nervous system with cognitive and/or psychiatric, central, and peripheral nervous is referred to as neurolupus [105] and has been reported to be associated with brain calcification up to 30% of patients [106].…”
Section: Classificationmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic autoimmune multifactorial disease characterized by multisystemic involvement and diverse clinical features [104]. Involvement of the nervous system with cognitive and/or psychiatric, central, and peripheral nervous is referred to as neurolupus [105] and has been reported to be associated with brain calcification up to 30% of patients [106].…”
Section: Classificationmentioning
confidence: 99%
“…It is interesting to note that imaging studies in neuropsychiatric SLE have shown cerebral atrophy, ventricular dilatation, cerebral edema, and cerebral infarction as well as intracranial hemorrhage. 9 Hence, the prominent ventricular system could be indicative of an impending neuropsychiatric involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Table (4). Focal fits were the commonest type of seizure representing 50% followed by generalized tonicclonic 33% and focal with secondary generalization 17% Table (5). There was an association between seizures and disease duration, diabetes mellitus, headache, cognitive impairment, cerebrovascular and MRI findings with significant predictor risk factor affecting seizures Table (6).…”
Section: 70%mentioning
confidence: 99%
“…Headache is rather a common complaint that can be associated with the disease. Most common types of headache are migraine with or without aura, tension headache and idiopathic intracranial hypertension [5] .…”
Section: Introductionmentioning
confidence: 99%